Social Conflict over the Establishment of Christian Houses of Worship in Aceh Singkil Regency (1979-2015) - Adelia Rizka; Bunari Bunari; Suroyo Suroyo (STKIP Taman Siswa Bima, 2025)
The conflict over the establishment of a Christian house of worship in Aceh Singkil Regency began in 1979, namely the plan to build the Indonesian Church of God (GTI) and the issue of spreading Christianity in Aceh Singkil by an Evangelist from the Indonesian Church of God in North Sumatra. This made the Muslim community restless and unacceptable. The Muslim community asked for the establishment of GTI to be canceled, but the restlessness and demands of the Muslim community were not responded to and were not responded to by GTI. The purpose of this study is to identify the beginning of the conflict, solutions to resolve the conflict, and to determine the impact of post-social conflict on interactions between religious communities and social relations in Aceh Singkil Regency (1979-2015). In this study, the researcher used a historical research method, namely collecting sources (heuristics), verification, interpretation and historiography. The results of this study indicate that (1) The social conflict related to the establishment of Christian houses of worship in Aceh Singkil Regency was motivated by the disappointment of Muslims towards Christians who did not obey the regulations of the Aceh Government, the majority of whose population is Muslim, (2) The provisions for the establishment of houses of worship in Aceh, (3) Peace efforts were made through dialogues between Muslim and Christian religious figures and accompanied by the Regional Government, (4) The conflict that occurred in Aceh Singkil Regency was not a conflict in the name of religion, but this conflict was based on the Church construction committee with regulations that had been made by the Aceh Regional Government which had autonomous powers to regulate its own regional affairs in the establishment of Christian houses of worship